Synthesis, Characterization, and Tribological Evaluation of TiO2-Reinforced Boron and Nitrogen co-Doped Reduced Graphene Oxide Based Hybrid Nanomaterials as Efficient Antiwear Lubricant Additives - Jaiswal V.; Kalyani; Umrao S.; Rastogi R.B.; Kumar R.; Srivastava A. (My University, 2025)
The microwave-synthesized reduced graphene oxide (MRG), boron-doped reduced graphene oxide (B-MRG), nitrogen-doped reduced graphene oxide (N-MRG), boron-nitrogen-co-doped reduced graphene oxide (B-N-MRG), and TiO2-reinforced B-N-MRG (TiO2-B-N-MRG) nanomaterials have been synthesized and characterized by various state-of-the-art techniques, like Raman spectroscopy, powder X-ray diffraction, scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy, high-resolution transmission electron microscopy, and X-ray photoelectron spectroscopy. Furthermore, the tribological properties of prepared nanomaterials as antiwear additives in neutral paraffin oil have been evaluated using a four-ball machine at an optimized additive concentration (0.15% w/v). The tribological parameters, like mean wear scar diameter, coefficient of friction, and wear rates, revealed that these nanomaterials have potential to be developed as environmentally friendly sulfated-ash-, phosphorus-, and sulfur-free antiwear lubricant additives. The friction- and wear-reducing behavior of MRG increased upon successive doping of nitrogen, boron, and both nitrogen and boron. Among these additives, B-N-co-doped MRG shows superior tribological behavior in paraffin base oil. Besides this, the load-carrying properties of B-N-co-doped MRG have significantly improved after its reinforcement with TiO2 nanoparticles. A comparative study of the surface morphology of a lubricated track in the presence of various additives has been assessed by SEM and contact-mode atomic force microscopy. The X-ray photoelectron spectroscopy studies have proved that the excellent lubrication properties of TiO2-B-N-MRG are due to the in situ formation of a tribofilm composed of boron nitride, adsorbed graphene layers, and tribosintered TiO2 nanoparticles during the tribocontact. Being sulfur-, halogen-, and phosphorus-free, these graphene-based nanomaterials act as green antiwear additives, protecting interacting surfaces significantly from wear and tear. © 2016 American Chemical Society.